Gender Motivations for TikTok Content Creation: A Comparative Study of Male and Female Students’ University Students - Ndou, Ananias; Magcaba, Mfanafuthi; Mthembu, Nompumelelo; Jugoo, Vikash; Mutanga, Murimo Bethel (Universitas Bina Darma, 2025)
TikTok has rapidly become a leading platform for youth self-expression and digital participation, yet little is known about how gender influences motivations for content creation. This study explores gender-based differences among South African university students, addressing a key gap in the literature. Using a mixed-methods design, 100 students (50 male, 50 female) were surveyed and focus groups with 25 participants were conducted to examine content types and motivational drivers, over a three-month period. Findings reveal clear distinctions: female students are primarily motivated by self-expression, social connection, and stress relief, favoring fashion, lifestyle, and dance content. Male students, by contrast, focus on entertainment, follower growth, and raising awareness, often creating comedy and educational videos. These patterns reflect broader social norms and platform dynamics, emphasizing different gratifications by gender. The study is guided by the Uses and Gratifications Theory in understanding these gendered motivations is essential for fostering more inclusive and responsive social media environments. It offers practical insights for educators designing digital literacy interventions, as well as for platform developers aiming to enhance inclusivity and user engagement.